Technical Challenges and Solutions for Super-Long Mountainous Tunnels at Great Depth - Yan Jinxiu (Geotechnical Engineering Journal of the SEAGS & AGSSEA, 2019)
There are various technical challenges faced by the construction of super-long mountainous tunnels at great depth, and also a series of new requirements for tunnelling arising from such aspects as geological investigation, construction duration, special geological conditions (high ground stress, high geothermal temperature and high-pressure groundwater), disaster prevention & evacuation and social development. Based on an analysis of the above-mentioned technical challenges, this paper presents technical views on solutions to those challenges and specifies the objectives of related technical development in the future. To improve the validity and accuracy of the geophysical prospecting, it is necessary to not only increase the accuracy of ground geophysical exploration at great depth, but also carry out research on the application of such techniques to tunnel investigation as airborne geophysical prospecting and HDD combined with borehole geophysical exploration. To maximize the benefits of tunnel projects, it is of importance that more attention should be paid to those issues relating to the tunnel design concept, such as the multiple functions of tunnel projects, energy saving and emission reduction, and environmental protection. As for tunnel support theories, in addition to optimizing the current theories, some unconventionally new lining theories need to be put forth to make the tunnel structure more durable and economical. It is also suggested that, in terms of construction, sustained efforts should be put into the development of innovative tunnelling techniques for a better, faster and more economical tunnelling, as well as the realization of intelligent mechanized tunnelling. When it comes to operation, it is obvious that there will be a trend towards intelligent maintenance in the future.